Clusters of preterm live births and respiratory distress syndrome-associated neonatal deaths: spatial distribution and cooccurrence patterns - Ana Sílvia Scavacini Marinonio; Daniela Testoni Costa-Nobre; Milton Harumi Miyoshi; Rita de Cassia Xavier Balda; Kelsy Catherina Nema Areco; Tulio Konstantyner; Mandira Daripa Kawakami; Adriana Sanudo; Paulo Bandiera-Paiva; Rosa Maria Vieira de Freitas; Lilian Cristina Correia Morais; Mônica La Porte Teixeira; et al. (BMC Public Health, 2022)
Abstract Background Prematurity and respiratory distress syndrome (RDS) are strongly associated. RDS continues to be an important contributor to neonatal mortality in low- and middle-income countries. This study aimed to identify clusters of preterm live births and RDS-associated neonatal deaths, and their cooccurrence pattern in São Paulo State, Brazil, between 2004 and 2015.  Methods Population-based study of all live births with gestational age ≥ 22 weeks, birthweight ≥ 400 g, without congenital anomalies from mothers living in São Paulo State, Brazil, during 2004–2015. RDS-associated neonatal mortality was defined as deaths < 28 days with ICD-10 codes P22.0 or P28.0. RDS-associated neonatal mortality and preterm live births rates per municipality were submitted to first- and second-order spatial analysis before and after smoothing using local Bayes estimates. Spearman test was applied to identify the correlation pattern between both rates. Results Six hundred forty-five thousand two hundred seventy-six preterm live births and 11,078 RDS-associated neonatal deaths in São Paulo State, Brazil, during the study period were analyzed. After smoothing, a non-random spatial distribution of preterm live births rate (I = 0.78; p = 0.001) and RDS-associated neonatal mortality rate (I = 0.73; p = 0.001) was identified. LISA maps confirmed clusters for both, with a negative correlation (r = -0.24; p = 0.0000). Clusters of high RDS-associated neonatal mortality rates overlapping with clusters of low preterm live births rates were detected. Conclusions Asymmetric cluster distribution of preterm live births and RDS-associated neonatal deaths may be helpful to indicate areas for perinatal healthcare improvement.